Health problems and health care practices of Lambani women of Gulbarga district - Prithviraj, Lucky; Murahari Naik, D (Recent Research in Science and Technology, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> Lambanis lead a gypsy life. Lambani community is characterized by distinct dress code and tattooing practice found among women. Women in this community contribute to family by accumulating needed resources especially from the forest. They often work in fields and in construction projects. Their active life style often disposes to some health problems apart from the forest. They often work in fields and in construction projects. Their active life style often disposes to some health problems apart from problems specific to women. With their close proximity to forest some health care practices involving herbs are commonly found among these women. These women are found to instinct tattoos on their skin to avoid some health problems is also common. A study involving Gulbarga district of Karnataka reveals that women belonging to Lambani community are following some herbal treatments to some common health problems. Toothaches, running nose, cough, cracked foot, stomach pain, white discharges are the main problems which were usually given herbal treatments. However, among the women about 32% to 52% belonging to different age groups are going to hospitals for treatments while others are depending on the herbal treatment. Even those who go to hospitals are found to follow certain herbal treatments which they think will bring cure. Further, strange practice of applying any crushed tablets sold in grocery shops for the treatment of headache and to treat eye troubles are also reported. A discussion has been made regarding the differences created with respect to effect increasing modern facilities on pertaining ethno-medical practices especially in tribes which depended on nature for the well being.